Potential extract of green algae (Ulva luctuca) as antimicrobial in mouthwash: literature review: Potensi ekstrak alga hijau (Ulva luctuca) sebagai antimikroba pada obat kumur: kajian pustaka - Andi M. Farhan; Andi Zaky Hanifan; Rifqiyanti Ismi; Al Fikriyani; Chanifah T. Maulita; Irene E. Rieuwpassa (Makassar Dental Journal PDGI Makassar, 2022)
Green algae as one of the marine natural resources which is included in the main seaweed is found in many coastal areas of In-donesia. The bioactive component that acts as an antibacterial agent in green algae type Ulva lactuca is ulvan polysaccharide extract. Ulvan is a cell wall polysaccharide that accounts for 9-36% dry weight of Ulva biomass and is mainly composed of rhamnose sulfate, uronic acid (glucuronic acid and iduronic acid) and xylose. Polysaccharide ulvan extracted from Ulva lactuca can be one of the antimicrobial materials used in mouthwash in dentistry.